IIBN (Indonesian Islamic Bibliographic Network): Solution to Minimize Information Access Gap among Islamic Universities in Indonesia (Prospect and Problem) - Ummi Rodliyah (Universiti Sains Islam Malaysia, 2024)
Presenter from Librarian at Sunan Ampel Islamic State Institution (IAIN Sunan Ampel Surabaya)